Performance-Related Pay and Objective Measures of Health after Correcting for Sample Selection - Nicole Andelic; Julia Allan; Keith A. Bender; Daniel Powell; Ioannis Theodossiou (Institute of Labor Economics (IZA), 2022)
Much of the literature on performance-related pay (PRP) and poor health relies on self-reported data, and the relationship is particularly difficult to examine due to confounding variables. To address these limitations we examine three groups of health measures using data from the UKHLS: blood pressure (n=5667), inflammation markers in blood (n=4025) and self-reported health (n=6120). Physiological markers of health allow us to circumvent some of the issues associated with self-reported measures and by using size of firm and % share of PRP workers in occupation we also statistically control for some of the endogeneity associated with self-selection bias. Regressions correcting for self-selection bias and socio-demographic covariates find that PRP contracts are associated with poorer self-reported mental health, higher systolic blood pressure and higher levels of fibrinogen. These findings have implications for firms that use PRP as they may need to implement policies to mitigate against stress.
Keywords: J33; M52; I1; 330; performance-related pay; health; sample selection